Transformação de olefinas alil aromáticas pela seqüência: hidroformilação / condensação de Knoevenagel / hidrogenação - Miguel de Araujo Medeiros (2006)
Alyl aromatic olefins, as eugenol, eugenol methyl ether and safrol havebeen submitted to a tandem process (hydroformylation/ Knoevenagelcondensation/ hydrogenation) to obtain products containing at least six extra carbon atoms. The process consists in the initial transformation of the olefin to an aldehyde through the [Rh(MeO)(COD)]2 catalyzed the incorporation of a carbon monoxide and a hydrogen molecules. Sequentially, the aldehyde is condensed with a compound containing an active methylene (acethylacetone, ethylacetoacetate, methylmalonate), generating a new functionalized olefin. This olefin is hydrogenated under the reaction conditions in a process catalyzed by the same rhodium complex employed in the hydroformylation. In order to optimize the conditions and improve selectivity to the desired products we study solvent effects, nature and concentration of the basic catalyst for the Knoevenagel condensation, as well as the phosphor auxiliary in thehydroformylation step. We found that best system employs eugenol as olefin, 1% mol/mol (in relation to the eugenol) of piperidine acetate, 3% mol/mol (in relation to the eugenol) of triphenylphosphine, 0,05% mol/mol (in relation to the eugenol) of [Rh(MeO)(COD)]2 in ethanol at 90°C.Under optimal conditions we obtained up to 83% of overall yield incondensation products.